Characterization and Genomic Features of the Enterococcus faecalis CTF3 Phage - Can Kurt, Kubra; Arslan, Ali; Tokuc, Edip; Kurt, Halil; Gonullu, Nevriye; Tokman, Hrisi Bahar (BILIMSEL TIP YAYINEVI, 2026)
Introduction: Enterococci are gram-positive, opportunistic pathogens that can be found in a wide variety of environmental settings. They cause many infections, such as sepsis, urinary tract infections, and endocarditis, in immunocompromised individuals and have developed resistance to currently used antibiotics. One alternative treatment method is bacteriophage (phage) therapy. The aim of our study is to isolate a new lytic phage against Enterococcus faecalis strains and determine its genomic characteristics. Materials and Methods: In this study, the E. faecalis phage CTF3 isolated from wastewater against the E. faecalis ATCC 29212 strain was obtained using the double-layer agar method; its whole genome was sequenced, and it was compared with other Enterococcus phages. Results: The E. faecalis CTF3 phage isolated in this study was identified as 40.215 base pairs in length and circular in structure. A total of 63 structural proteins were identified in the phage genome. Considering the phylogenetic placement and taxonomic classification of the E. faecalis CTF3 phage, it is concluded that the isolated phage may be a novel Enterococcus phage belonging to the class Caudoviricetes and the genus Efquatrovirus. Conclusion: A new lytic phage effective against E. faecalis, a nosocomial infection agent, has been isolated from wastewater and its whole genome characteristics have been characterized. It is thought that the data obtained from this study could guide clinicians in creating a phage library for future phage therapy applications and clinical use.
Keywords: Enterococcus faecalis; Lytic phage; Multidrug resistance; Phage therapy; RESISTANCE; EMERGENCE; Microbiology